If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3k + 3 + 5k = 9 Reorder the terms: 3 + -3k + 5k = 9 Combine like terms: -3k + 5k = 2k 3 + 2k = 9 Solving 3 + 2k = 9 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2k = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 2k = 9 + -3 2k = 9 + -3 Combine like terms: 9 + -3 = 6 2k = 6 Divide each side by '2'. k = 3 Simplifying k = 3
| 2(1X+6)=10 | | -4m-1.1m+11+3.4m-16.1= | | 3(6-2y)-y=4 | | 5t^2+8t-10=0 | | -32=8-2k | | 1/x=213 | | 67=-3-10r | | h(t)=60x-16x^2 | | x^2+2000*x+100000000=0 | | 2sin=2cos(2x) | | 126=7x+5+4x | | 4x+5=2(3x-7)-3 | | 2x+14+3x+11=180 | | x+-9=-36 | | x^2+(7+a)x+7a=0 | | 2-3m=(-10) | | 3/4x-(-16)=28 | | 2-5(11a-3)= | | x^2+20000*x+100000000=0 | | -2x-5-x=20 | | z=0.39 | | -2x-5-x=-20 | | z=1.26 | | 140-y=254 | | (x^5-x)/x^4 | | 1+2x-6x=-23 | | (X-3)(x-8)=-30 | | 3•5^x/5-4=13 | | 3y=9+15 | | -7+2x+x=11 | | (n+6)=7n+42 | | =849-2(18.4282) |